Metaheuristic Strategy for Dynamic Traffic in Wavelength Division Multiplexing Optical Networks (Wdm) [Estrategia Metaheurística Para Redes Ópticas Sin Conversión de Longitud de Onda Con Tráfico Dinámico (Wdm)] - Rodriguez-Garcia, A (Centro de Informacion Tecnologica, 2016)
This research shows the performance comparison between different heuristics such as genetic algorithms, simulated annealing, Tabu Search, Snake-One and a new metaheuristic called Snake-Two. Earlier were obtained low blocking probability but with a tendency to increase network utilization. The new Snake-Two strategy can prove that the behavior of the blocking probability decreases at low network usage. These results are compared with a conventional algorithm that was used to visualize the improvement of each indicator. The indicators used for comparison, are the blocking probability and the network utilization and a new indicator called Heuristic Algorithm Rate. This strategy proposes using the congested links, allowing increasing the traffic in some areas, and reducing it in other areas. The results are promising to achieve lower blocking probability but the tendency of increasing the use of the network resources continues.